Innovating Elderly Clothing Features for Enhanced Wearability Using A Design Thinking Approach - Hanifah, Harum Iffah; Soewardikoen, Didit Widiatmoko; Azhar, Hanif; Rahman, Yanuar (Sahabat Publikasi, 2025)
Elderly individuals aged 60 and above often encounter various challenges in daily activities, such as dressing up. These challenges include difficulties in donning and doffing clothing, the need for frequent changes of clothes, struggles with clothing due to tremors, and obstacles faced by some elderly individuals when dressing while seated. As individuals age, there is typically an increase in their level of dependency. This case research is conducted at the Panti Sosial Tresna Werdha Budi Pertiwi (Elderly Care home) in Bandung, focusing on the design of adaptive clothing. Utilizing a design thinking approach, this research identifies the challenges and needs of the elderly population. The design thinking process includes data collection through observations and interviews, analyzing the primary needs of the elderly, ideating and developing potential solutions, and conducting testing with prospective users. The research addresses six key aspects: comfort, ease of use, flexibility of movement, aesthetic appeal, convenience in storage and washing, and safety to minimize the risk of injury. This research was performed to develop adaptive clothing that simplifies the elderly's dressing and undressing process. The adaptive clothing design aligns with the United Nations Sustainable Development Goal (SDG) on “Good Health and Well-being” by enhancing the quality of life for the elderly through tailored designs that cater to their unique needs.